KONTRIBUSI PEKERJA PEREMPUAN DAN BELENGGU PERAN KULTUR (STUDI KASUS BAGI PEKERJA PEREMPUAN PEMBERSIH JALAN DESA MKCM PUNE KABUPATEN HALMAHERA UTARA) - Novriani Monika Wangka (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
This study aims to examine the contribution of female workers and the shackles of the cultural role (case study for MKCM Pune village road cleaning workers). This research is a qualitative research. The informants taken in this study were female workers in Pune MKCM village road cleaners totaling 14 people. Then the samples taken using a purposive method by considering married female workers and Suda bekeja for more than 2 years, amounting to 6 street cleaning women workers. The results of this study found that, all female MKCM Pune village workers were married, and had worked more than 2 years. This is evidenced by the response or response given by Pune female MKCM village road cleaners who have shown how much they care about the family's economy even though they often carry out conflicts (differences of opinion) between husband and wife. This can occur because of various factors that are background, such as work time which starts at 3:00 a.m. and takes place at 8:00 a.m. and at dusk starting at 6:00 p.m. to 7 p.m. The occurrence of opinion differences is motivated by the shackles of the role of culture that has compelling values and norms. To overcome this, road-winning female workers from the MKCM Pune village of North Halmahera Regency, strive to remain steadfast, and continue to explain the work time owned by workers women whose main tasks are as street cleaning women workersKeywords: Female workers, culture, MKCM Pune